Pengaruh KIE terhadap Pengetahuan Masyarakat tentang Penggunaan Obat Anti Nyeri di Desa Buluagung - Setyowati, Lisus; Cahyanti, Diana; Rosida, Rosida (UI Scholars Hub, 2023)
Background. Improper use of painkiller can lead to increased morbidity and death rates and decreased quality of life, The high percentage of self-medication carried out by the community shows the importance of medical education to determine the level of rationality of treatment performed. Information Communication and Education (ICE) a message to others with the aim of informing. Objective. To asses level of knowledge and effect of ICE on the use of painkiller drugs in Buluagung Village, Siliragung District, Banyuwangi Regency. Method. This study is a quantitative, pre-experimental research with one group pre-test and post-test design. The research sample used 80 respondents was obtained by the Slovin formula from the population of Buluagung Village. This study used ICE as an intervention and questionnaires to collect data from respondents. The data analysis used Wilcoxon test. Results. The pre-test results stated that was still lacking in knowledge. Intervention in the form of ICE is one of the efforts to increase community knowledge about the use of painkiller drugs. After being given treatment, study shows good results in the post-test. From data analysis, it can be concluded that there is an influence of ICE on the use of painkiller drugs.